Exchange rate arrangements in the run-up to the EMU: some experience in currency board countries - Julda Kielyte (Economics and Econometrics Research Institute (EERI), 2002)
Since the beginning of the transition process from centrally planed to market economies, East European countries have experienced relatively high inflation and a market depreciation of their currency. Their monetary systems have gone through dramatic changes in the recent ten years, making the transition from a mono-bank to the traditional autonomous central bank. Some have adopted a currency board arrangement (CBA). Three candidate countries to the European Union (EU) - Bulgaria, Estonia and Lithuania -face the perspective of becoming a full-fledged members of the EU and after of the European Monetary Union (EMU). This paper investigates the issues and advantages of CBAs, especially in three transition countries (Estonia, Lithuania and Bulgaria) in the context of accession to the EU and to the European Monetary Union (EMU).
Keywords: E42; E52; E61; F33; 330; European Monetary Union; currency board arrangement; Exchange rate arrangements; CEE